THE IMPLEMENTATION OF PEER TEACHING IN TEACHING ENGLISH FOR YOUNG LEARNERS OF ENGLISH DEPARTMENT, UNIVET SUKOHARJO - Nurnaningsih (University of Surakarta, 2020)
The objective of the study is to identify the application of Peer Teaching in the subject of Teaching English for Young Learner (TEYL) and combined it with teaching media that suitable for the teaching material. Besides it also observed the dominance of teaching media that were used by students in TEYL. It is a qualitative method. The subject of the study is 6th semester students of English Department. The collecting data of the study are observation, interview, and documentation. The application of Peer teaching in the study are 1) making sure that peer teacher mastered the teaching material, 2) using system reward, 3) using positive reinforcement, 4) choosing the appropriate exercise, 5) using grouping strategy, 6) using role play of peer teaching, 7) forcing on feedback that was given by the lecturer. Then the dominant teaching media used in peer teaching is downloaded video from YOUTUBE. The reason was easier to get and it is also cheap.